The Martyr Hadi Abd-el-Hussein Abood Al-Shahtoor (1940-1982 ) (A Historical Study ) - السعيدي أ.م.د.أركان مهدي عبد الله (Thi Qar Arts Journal, 2021)
Souq Al-Shuyukh is considered one of the ancient Iraqi cities for its authenticity and famous for its writers and scholars until it was called ((Najaf Al Thaniya)), due to its cultural and intellectual characteristics that the city of Najaf approached in the many scientific families, religious councils and literary clubs, and among its scientific families the family of Shahtour emerged. That inhabited the city of Souk Al-Shuyukh and gave birth to several scholars and virtues who had a distinguished role in the intellectual and scientific life of the city. Among the sons of this family, the martyr Hadi Abdel-Hussein Al-Shahtour has emerged as a personality distinguished by its high Islamic culture and kinetic activity in the management of Islamic work To study the personality of the martyr Hadi historically, the research was divided into three topics: the first studied its lineage, its social origin and the religious and scientific status of its family. As for the second topic, it was devoted to showing its political work and Islamic activity, which was represented in its affiliation with the Liberation Party and then to the Islamic Dawa Party, and the third topic dealt with his arrests At the hands of the Baathist regime, which ended with his imprisonment and then his execution